Identification of two distinct pathways of human myelopoiesis - Drissen, R; Thongjuea, S; Theilgaard-Mönch, K; Nerlov, C (American Association for the Advancement of Science, 2019)
Human myelopoiesis has been proposed to occur through oligopotent common myeloid progenitor (CMP) and lymphoid-primed multipotent progenitor (LMPP) populations. However, other studies have proposed direct commitment of multipotent cells to unilineage fates, without specific intermediary lineage cosegregation patterns. We here show that distinct human myeloid progenitor populations generate the neutrophil/monocyte and mast cell/basophil/eosinophil lineages as previously shown in mouse. Moreover, we find that neutrophil/monocyte potential selectively cosegregates with lymphoid lineage and mast cell/basophil/eosinophil potentials with megakaryocyte/erythroid potential early during lineage commitment. Furthermore, after this initial commitment step, mast cell/basophil/eosinophil and megakaryocyte/erythroid potentials colocalize at the single-cell level in restricted oligopotent progenitors. These results show that human myeloid lineages are generated through two distinct cellular pathways defined by complementary oligopotent cell populations.